(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2017)
In this present innovatively superfast world, where the snap of catches is changing the manner in which individuals think, design and execute their works and experience their lives, virtual reality, surrealism, hyper reality are the terms in vogue. They are so commonly utilized wherever that they may not appear to be whimsical any more. In any case, the fervor in superstitions, magic in such a context the novel by Chitra Banerjee Divakaruni, The Mistress of Spices, is a superb perused which besieges the faculties and shivers the craving with its fascinating utilization of spices. The spices are not utilized simply to upgrade flavors to detonate on the taste buds yet assume a vital part in the improvement of the novel. They loan a magical quality and are a methods through which magic realism is utilized as a part of the novel. Divakaruni’s most noteworthy resource is her style since she is offered with a natural feeling of mixing reality and creative energy, the past and the present, fantasy and beliefs. In this thesis We have discussed Magic Realism, Mistress of Species, the Mirror of Fire and Dreaming ,Conch of Bearer and Elements of Magic and Power of her novels.